2003
DOI: 10.1002/chin.200322292
|View full text |Cite
|
Sign up to set email alerts
|

Some New Views on the Tautomerization Mechanism

Abstract: Theoretical chemistry Theoretical chemistry Z 0350 Some New Views on the Tautomerization Mechanism -[107 refs.]. -(KERESELIDZE, J. A.; ZARQUA, T. S.; KIKALISHVILI, T. J.; CHURGULIA, E. J.; MAKARIDZE, M. C.; Russ. Chem. Rev. (Engl. Transl.) 71 (2002) 12, 993-1003; Dep. Chem., Javakhishvili State Univ., Tbilisi 380028, Georgia; Eng.) -Lindner 22-292

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For 2-substituted pyridines 21a, 23a and 26a, the proton transfer was calculated with the use of a dimeric mechanism in the reaction coordinate mode (R NH ). 87 For the tautomersation of 4-substituted pyridines 22a and pyridinethiones 24a, the proton transfer through a dimeric mech- anism is sterically hindered. In this connection, we proposed a trimeric mechanism for the proton transfer in compounds 22a and 24a.…”
Section: Tautomerism In Pyridinesmentioning
confidence: 99%
“…For 2-substituted pyridines 21a, 23a and 26a, the proton transfer was calculated with the use of a dimeric mechanism in the reaction coordinate mode (R NH ). 87 For the tautomersation of 4-substituted pyridines 22a and pyridinethiones 24a, the proton transfer through a dimeric mech- anism is sterically hindered. In this connection, we proposed a trimeric mechanism for the proton transfer in compounds 22a and 24a.…”
Section: Tautomerism In Pyridinesmentioning
confidence: 99%
“…An intermolecular mechanism of proton transfer (H atom) is proposed for imidazole by quantum mechanical calculations . The one‐step intramolecular mechanism is energetically unfavorable, but the one‐step proton transfer in a trimer or the successive two‐step proton transfer in dimers from the 1‐position (structure I) to the 2‐position (structure II) and then to the 3‐position (structure III) is energetically favorable for imidazole . Vibrational spectroscopy (IR and Raman) study also showed that the intramolecular proton transfer via a two‐step transfer involving the intermediate structure II is possible in vibrationally excited states in which the energy barrier between structures I and II is either significantly decreased or nonexistent.…”
Section: Resultsmentioning
confidence: 99%
“…It is presently known that the ground state proton exchange between N3 and N1H is so fast that the mixture of tautomers behaves like a pure compound in a magnetic field. An intermolecular mechanism of proton transfer (H atom) is proposed for imidazole by quantum mechanical calculations . The one‐step intramolecular mechanism is energetically unfavorable, but the one‐step proton transfer in a trimer or the successive two‐step proton transfer in dimers from the 1‐position (structure I) to the 2‐position (structure II) and then to the 3‐position (structure III) is energetically favorable for imidazole .…”
Section: Resultsmentioning
confidence: 99%